Applying Psychological Science to Examine Prospective Memory in Simulated Air Traffic Control. (October 2014) - Loft, Shayne
Failures to remember to perform deferred task actions in work settings such as air traffic control can have serious consequences. Most research examining the cognitive mechanisms underlying prospective memory has used simple, static tasks, which may make it difficult to generalize results to work settings. I describe a body of research that has applied theory and methods from the basic prospective-memory and attention-capture literatures to simulations of air traffic control. These theories and methods can be used to anticipate many findings, such as the finding that prospective-memory demands incur performance costs in ongoing air traffic control tasks, and that prospective-memory error and costs to ongoing air traffic control tasks can be reduced by the use of spatial context or prospective-memory aids. Research in laboratory settings that simulates work contexts such as air traffic control can both establish the utility of psychological theory and produce application-relevant information.